Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-07T17:34:08+01:00
S=a*b- wyliczyć b
b=S/a

a=b*h:2 wyliczyć h
2a=b*h/:b
h=2a/h

V=⅓ Q*H//*3
3V=Q*H //:Q
H=3V/Q wyliczyć H

S=(a+b)h:2
S=ah+bh :2 //*2
2S=ah+ab
2S-ah=ab //:a
(2S-ah)/a=b


ax+c=c
ax=c-c
ax=0
x=0

a:x+b=c
a/x=c-b //:a
x=(c-b)/a

2010-01-07T17:34:38+01:00
S=a*b- wyliczyć b /:a
S/a = b
a=b*h:2 wyliczyć h /*2
2a=b*h /:b
2a/b=h
V=⅓ Q*H wyliczyć H /*3
3V= Q*H /:Q
3V/Q
S=(a+b)h:2 wyliczyć b
S = ah + bh : 3 /x3
3S = ah + bh
3S = h(a + b) /(a+b)
3S/(a+b) = h
ax+c=c wyliczyć x
a:x+b=c wyliczyć x
a:a-t=b:b-t wyliczyć a